Philosophical Risk Transformation: A Systematic Review From Protection to Radical Adaptation in Indonesian Coastal Ontology - Deni Sabriyati; Haznah Faizah AR (Journal of Maritime Policy Science, 2025)
Coastal regions in Indonesia are increasingly exposed to compound climate-related hazards sea-level rise, erosion, storm surges, and saltwater intrusion while also facing strong anthropogenic pressures, creating not only a management problem but a deeper philosophical crisis about how risk, nature, and human agency are understood.  Against this background, this study aims to systematically examine the philosophical transformation of coastal risk governance from a technocentric Protection, paradigm toward, Radical Adaptation within Indonesian coastal ontology, addressing the gap in philosophical (ontological, epistemological, and ethical) analysis of this transition.  Methodologically, the article applies a systematic literature review, synthesizing 94 selected sources (2010–2025, with seminal works for foundations) gathered through database searches (Scopus, Web of Science, ScienceDirect, and Garuda) and supplemented by semantic search, followed by structured extraction and content analysis using a priori thematic coding across ontology, epistemology, and axiology or ethics.  The findings indicate a clear shift in scholarship and practice: conventional protection strategies centered on engineering control are increasingly inadequate under accelerating uncertainty, while radical adaptation reframes risk as an intrinsic feature of coastal existence that requires coexistence, relationality, and transformative learning rather than defending the status quo.  This transformation is marked by (1) an ontological move from separation/domination to living-with-risk, (2) an epistemological move toward hybrid knowledge that integrates scientific approaches traditional ecological wisdom, (3) an ethical reorientation toward ecological solidarity, intergenerational justice, moral responsibility